REALISASI GERAKAN LITERASI DIGITAL SEBAGAI IMPLEMENTASI GERAKAN LITERASI NASIONAL DI SEKOLAH MUHAMMADIYAH PANGKALAN BUN - Putri, Izzah Iswara Mundhofir; rmiyanti, rmiyanti; Ningsih, Endang Rahayu (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The problem of this research is how the realization of the digital literacy movement as a form of implementation of GLN in Muhammadiyah Pangkalan Bun School and what factors influence the implementation of digital literacy at Muhammadiyah Pangkalan Bun School. This research method is descriptive qualitative, which describes factually the factors that influence the implementation of digital literacy at Muhammadiyah Pangkalan Bun School. Data collection was carried out by means of observation, interview and questionnaire distribution. The data analysis of this research was carried out inductively, namely the analysis technique that went from fact to theory. This study uses theoretical triangulation, which is to double-check the validity of the research data with existing related theories. The results of this study indicate that digital literacy at Muhammadiyah Pangkalan Bun School is realized in the form of hardware such as laptops, projectors, speakers, and WiFi. Several factors influence the implementation of digital literacy, namely: (1) The location of the school which is the access in and out of the general public. (2) The location of the school which is one area with a lower level of school (TK ABA, SD Muhammadiyah Pangkalan Bun, SMP Muhammadiyah Pangkalan Bun). (3) Different students' backgrounds.